Aerodynamic effects of surface deformities on aerofoils for low-speed stratospheric flight. (January 2023) - Kimmons, Jeremy; Thomas, Peter; Colonia, Simone
High-altitude pseudo-satellites are an expanding focal area of the aerospace industry which require new technologies and manufacturing processes to reduce weight and increase efficiency with the aim of increasing endurance. One such process has resulted in the occurrence of small deformities along the leading edge of a lightweight unmanned aerial vehicle structure with the application of its skin, which may have a detrimental impact on its performance and efficiency. This paper focuses on the effects of these manufacturing deformities on the aerodynamic performance of the vehicle's aerofoil when operating in low Reynolds number flow with the intention of identifying any detrimental flow variation. This analysis is achieved by comparing the lift curve, drag polar and pressure coefficient of both the deformed and undeformed cases of two aerofoils: a SG6042 and a GOE 523. This is accompanied with an examination of the local flow conditions scrutinising the near-wall y + and turbulent kinetic energy calculations. The investigation finds that in two-dimensional flow, the deformities replicate the effects of transition trips in the shrinking or elimination of laminar separation bubbles. At Reynolds numbers below 250, 000, the deformities reduce the net drag while leaving the lift largely unaffected. However, as a result, there is a slight shift in the minimum power condition in the order of 8% which would produce some performance loss for power efficiency and endurance.